2006
DOI: 10.1002/mds.20767
|View full text |Cite
|
Sign up to set email alerts
|

Globus pallidus deep brain stimulation in dystonia

Abstract: Globus pallidus deep brain stimulation (GPi-DBS) is a useful alternative in the treatment of dystonia. Patients selected for GPi-DBS were prospectively rated with the Unified Dystonia Rating Scale (UDRS). Also, "blinded" videotape assessments were performed. Eleven patients were identified. Compared with pre-DBS scores, there were improvements in mean total UDRS score (15.3%) and in the following subscores: neck (18.18%), trunk (32.9%), arm (17.9%), and leg (19.9%). One patient developed a skin infection and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 15 publications
5
28
1
Order By: Relevance
“…Despite previous reports [11,13,16,23,24] , in our case series the clinical results were statistically significant also in facial movements and speech production even 5 years after surgery (speech/swallowing, 58% at 3 years and 55% at 5 years; table 2 ; fig. 4 , online supplementary video 1; for all online supplementary material, see www.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Despite previous reports [11,13,16,23,24] , in our case series the clinical results were statistically significant also in facial movements and speech production even 5 years after surgery (speech/swallowing, 58% at 3 years and 55% at 5 years; table 2 ; fig. 4 , online supplementary video 1; for all online supplementary material, see www.…”
Section: Discussioncontrasting
confidence: 53%
“…Deep brain stimulation (DBS) has emerged in the last 10 years as an effective and reversible therapeutic option for patients with medically refractory dystonia [7][8][9][10][11][12] . The posteroventral globus pallidus internus (GPi) is the main target for treatment of primary dystonia as demonstrated by different authors [13][14][15][16] . However, only few case series have been reported in the literature analyzing long-term follow-ups of patients treated with GPi DBS for focal or segmental dystonia [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally if one further segregated our data to only include DYT-1 primary generalized cases, the benefit jumped to 48%. Table 9 continued Author Type of study Type of dystonia Though the UDRS is less utilized, our study coupled with those from Grips [18], Diamond [14], Evidente [17] and Margarinos-Ascone [35] demonstrates that UDRS findings are comparable to BFMDRS-M score reports in accuracy and reliabililty. In our study, both the UDRS and BFMDRS-M measured the severity and duration of dystonia.…”
Section: Discussionsupporting
confidence: 72%
“…After that, two multicenter studies on bilateral Globus Pallidus pars Interna (GPi) DBS have demonstrated convincing clinical benefit on a large number of patients with primary generalized/segmental dystonia [7][8][9]. Accordingly, GPi DBS was approved by FDA in 2003 (as a humanitarian device exemption) for patients with chronic, medically intractable dystonia [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%